Révolution sociale et utopie chez les premiers Fabiens (1884-1890) : un positionnement complexe - Marie Terrier (Cahiers Victoriens et Edouardiens)
Forty years after the demise of Owenism and about ten years after the dissolution of the First International (the IWMA) in the wake of the Paris Commune, there was a Socialist Revival in Britain. It is in this context that the Fabian Society was created in 1884. Its members were liberal, middle-class reformers. They aspired to a social revolution: they wished for a wide-ranging change in the social and economic organisation. The ambition of the Fabians was to offer a theoretical basis to British socialism. In the process, they were soon faced with the question of utopias. Their position was rather complex. On the one hand, they openly sought to distinguish themselves from early 19th-century socialism that had been called ‘utopian’. And they criticised the methods of utopian thinkers. On the other and they were ready to acknowledge the value of utopias as they gave encouragement to the idea that the world could be changed. Additionally, even if the Fabians distanced themselves from Owenism, often criticised as ‘utopian’, they still held favourable views on Owen and his followers. While in another way, as the Fabians were convinced that a better world was reachable, some of their ideas can be called utopian. Studying their position on the question of utopias will allow us to underline the limited impact of Marxism on their thought, but it will highlight John Stuart Mill’s influence. The Fabians’ criticism of utopias will also reveal their reformist political strategy and their evolutionist vision of social change.